Role of Serum Ceruloplasmin as Tumor Marker in Early Diagnosis of Oral Squamous Cell Carcinoma (Medical Forum Monthly, 2021)
Objective: To compare serum Ceruloplasmin (CP) levels in histopathologically diagnosed oral squamous cell carcinoma (OSCC) patients with healthy controls and to determine its role as tumor marker of early diagnosis and malignant transformation of OSCC.Study Design: Comparative cross-sectional studyPlace and Duration of Study: This study was conducted at Department of Oral Pathology and Oral & Maxillofacial Surgery, King Edward Medical University Lahore, in duration of 6 months from February 2019 to August 2019.Materials and Methods: Sample size of 90, compromising: control group A, 45 healthy subjects; group B, 45 histopathologically diagnosed OSCC patients were included. After obtaining informed consent from all patients, serum CP levels were estimated by using immunoturbidimetric analysis for quantitative determination of CP level on the serum samples. All the data was collected on predefined pro-forma and analyzed using SPSS version 26. The mean values of CP were compared using ANNOVA and One-way ANNOVA test. Independent T-Test was applied to subgroups of OSCC to analyze the OSCC disease progression.Results: CP levels were significantly increased in histopathological grades of OSSC in comparison to control group (p-value < 0.001). However, there was no significant difference between CP values of well differentiated and moderately differentiated histopathological grades of OSCC.Conclusion: Serum CP levels can help to diagnose early stages of OSCC, thus establishing it as noninvasive tumor marker of malignant transformation. However, role of serum CP levels to establish progression of disease is still ambiguous.